From loose sand to sandstone: An experimental approach on early calcite precipitation in sands of siliciclastic and mixed carbonate-siliciclastic composition - Janßen, Meike; Caracciolo, Luca; Bonnell, Linda M.; Lander, Robert H.; Adelhardt, Philipp; Moldenhauer, Lara; Munnecke, Axel; van Geldern, Robert; Stollhofen, Harald (PLoS ONE, 2024)
Artificially cemented sandstones were produced to assess the impact of detrital texture and composition on the precipitation and distribution of early calcite cement, and cement-related degradation in porosity. To simulate early-calcite cementation, loose sediment of variable composition (siliciclastic and calcareous) and grain size was exposed to a calcite supersaturated solution for 35 to 58 days at 23◦C. Identification and distribution of the newly precipitated crystals was performed with high resolution 2D optical and scanning electron microscopy. The experimental results show the precipitation of grain-coating, pore-bridging and pore-filling granular calcite cement with up to 100 μm crystal size. Despite a positive correlation between the amount of detrital carbonate grains and calcite crystals, calcite cement does not preferentially nucleate on bioclast surfaces, irrespectively of their favourable mineralogy. Siliciclastic grains show high calcite cement coverage with altered feldspar, particularly plagioclase, displaying coverage of 94.3%. Grain size variations within the sand packs have influence on the precipitation pattern of calcite with coarse-grained layers (500–710 μm) showing minor calcite cementation (6.3%), while medium- (250–500 μm) to fine-grained layers (125–250 μm) comprise average calcite cement contents of 16.3% and 28.2%, respectively. The findings of this study enhance our knowledge regarding the precipitation processes of calcite in porous material with heterogeneous reacting mineral phases, shapes and pore connectivity.
CRIS-Team Scopus Importer:2024-11-08